Sickness and quarantine allowance for farmers during the COVID-19 pandemic - Puślecki, Damian (Przegląd Prawa Rolnego, 2021)
The aim of this paper is to determine to what extent the benefits for farmers insured in the Agricultural Social Insurance Fund that have recently been granted provide protection during the COVID-19 pandemic. The conclusion is that the current regulation does not provide insured farmers with sufficient protection against a temporary loss of capacity to work. The benefits granted in the form of COVID sickness and quarantine allowance constitute a too modest social support for agriculture during the pandemic. These allowances fail to take into account the specificity of work in agriculture and do not compensate for the farmer’s lost income and, having been rather carelessly adopted from the universal system of insurance, they do not fulfil their functions properly. In view of the fourth wave of infections, it is necessary to amend these measures as soon as possible.